فقه الإمام إبراهيم النخعي وأثره في مذهب الحنفية في صفة الصلاة: Al-Imam Ibrahim al-Nakha’i’s Jurisprudence and Its Impact on the Hanafi School of Thought in the Description of the Salah (Prayer) - Arben Ghani Ahmetay (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The research aims to: - Introduce Imam Ibrahim al-Nakha'i (may Allah have mercy on him) through a brief biographical sketch. -Compile his jurisprudential views on a section of the Book of Prayer, study the issues therein, and clarify his positions. -Uncover the methodology of Imam al-Nakha'i (may Allah have mercy on him) and its relation to the ijtihadi approach of the Hanafi school.The research adopts an inductive and deductive methodology. The findings reveal a significant influence of his jurisprudence on the Hanafi school, as they concurred with him in seven out of eight issues examined. Two of these are unique to the Hanafis, who disagreed with the majority in favor of Imam al-Nakha'i's opinion. They disagreed with him on only one issue, yet even in that, they agreed with a less well-known narration attributed to him. Furthermore, they aligned with him on numerous evidentiary sources in Islamic law, including the Qur’an, Sunnah (particularly mursal hadith), consensus (ijma‘), analogical reasoning (qiyas), and the statements of the Companions. This research highlights the impact of Imam al-Nakha‘i’s jurisprudence—may Allah have mercy on him—on the Hanafi school, both in its foundational principles and practical rulings.